Distribution, trends, and antifungal susceptibility of Candida species causing candidemia in Japan, 2010–2019: A retrospective observational study based on national surveillance data. (12th September 2022) - Kajihara, Toshiki; Yahara, Koji; Nagi, Minoru; Kitamura, Norikazu; Hirabayashi, Aki; Hosaka, Yumiko; Abe, Masahiro; Miyazaki, Yoshitsugu; Sugai, Motoyuki
Abstract: The increasing incidence of candidemia and the emergence of drug-resistant Candida species are major concerns worldwide. Therefore, long-term surveillance studies are required. Here, we provide one of the largest longitudinal overviews of the trends in the prevalence of Candida species using national data of 57 001 candidemia isolates obtained from > 2000 hospitals for the 2010–2019 period in the Japan Nosocomial Infections Surveillance database. The proportion of Candida species, except Candida krusei and Candida guilliermondii, was almost the same during the study period. The proportion of C. guilliermondii surpassed that of C. krusei in 2014. The incidence of candidemia due to C. albicans ( P  < 0.0001), C. parapsilosis ( P  = 0.0002), and C. tropicalis ( P  < 0.0001) have decreased significantly over this period. Azole susceptibility of C . tropicalis was low, with 17.8% of isolates resistant to fluconazole and 13.5% resistant to voriconazole. The micafungin susceptibility of C. glabrata was low, with 8.0% of isolates showing resistance. The resistance rate of C. krusei toward amphotericin B fluctuated considerably (between 3.2% and 35.7%) over this period. The incidence rate of candidemia caused by C. parapsilosis and C. guilliermondii in hospitals responsible for bone marrow transplantation was significantly higher than that in other hospitals. Overall, our study suggests that in Japan, the species distribution of Candida was almost the same in this period and similar to that reported in North America and Europe. A relatively high resistance to azoles and micafungin was observed in C. glabrata, C. tropicalis, and C. krusei isolates, which require continued surveillance. Lay Summary: This study verifies that the proportion of Candida species in Japan was almost the same from 2010–2019. A relatively higher resistance to azoles and micafungin was observed for C. glabrata, C. tropicalis, and C. krusei isolates.